Physiological age in Lutzomyia youngi (Diptera: Psychodidae) populations from an endemic area for cutaneous leishmaniasis, Venezuela Edad fisiológica de poblaciones de Lutzomyia youngi (Diptera: Psychodidae) de una área endémica de leishmaniasis cutánea - José V. Scorza; Milagros Oviedo (Universidade de São Paulo, 1994)
Batches of sylvatic females of Lutzomyia youngi (Phlebotominae) captured in a Shannon trap on twelve occasions over one year in a locality where subcutaneous leishmaniasis is endemic, near the city of Trujillo, Venezuela, were used to study: 1) the percentages of parous females according to previously established criteria and 2) the average number of eggs laid spontaneously by isolated females during 7 days after feeding on hamsters. The data on the batches of females captured on nights previous to the rainy period (prepluvial) were compared with those on females captured after the rains (postpluvial) . Significant differences were detected by variation analysis for two variables and different number of N, as also were consistent groupings by Duncan's Test for pre-and postpluvial lots of females. The females captured on nights prior to the rainy periods (January-March and August-September) presented higher rates of nulliparity (86-72%) and contained or laid a greater number of eggs (71-67) than those captured after the rains (March-June and November-December) which presented lower rates of nulliparity (60-24%) and a smaller number of eggs (50-30). The rainfall peaks occurred in April and September-October, respectively. It is considered that these differences can be used by epidemiological studies as a means of estimating the physiological age of female populations of L. youngy. Con lotes de hembras silvestres de Lutzomyia youngi (Phlebotominae) capturadas con trampa de Shannon en doce ocasiones a lo largo de un año, en una localidad endémica para leishmaniasis tegumentaria, próxima a la ciudad de Trujillo, Venezuela, se estudio: 1) los percentajes de hembras paridas según criterios previamente establecidos y 2) el número medio de huevos puestos espontaneamente por hembras aisladas, en el curso de 7 días postigestión, ingurgitadas también sobre hámsteres. Se comparó la data de lotes de hembras capturadas, en noches de días anteriores a los períodos de lluvias (prepluviales) con las de hembras capturadas después de las lluvias (postpluviales). Se detectó diferencias significativas por análisis de varianza para dos variables y diferente número de N, y también consistentes agrupaciones con la prueba de Duncan para lotes de hembras pre y postpluviales. Las hembras capturadas en noches previas a los periodos de lluvias (Enero - Marzo y Agosto - Septiembre) exhibieron más altas tasas de nuliparidad (86-72%) y contuvieron o eliminaron mayor número de huevos (71-67), que las hembras capturadas después de las lluvias (Marzo-Junio y Noviembre - Diciembre), con mas bajas tasas de nuliparidad (60-24%) y menores números de huevos (50-30). Los picos de lluvias ocurrieron en Abril y Septiembre - Octubre, respectivamente. Se considera que estas diferencias puedan ser utilizadas, como una estimativa de la edad fisiológica de problaciones de hembras de L. youngi, en estudios epidemiológicos.